1991
DOI: 10.2105/ajph.81.10.1307
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of intravenous drug users in Rome: a cohort study.

Abstract: A historical cohort study was carried out in Rome to examine overall and cause-specific mortality among intravenous drug users (IVDUs). A total of 4200 IVDUs (3411 men and 789 women) enrolled in methadone treatment centers between 1980 and 1988 were studied. There were 239 deaths during the follow-up period. The overall SMR was 10.10 in the entire cohort (95% confidence interval, 8.86-11.47), 9.30 in males and 18.07 in females. A large excess of mortality in both sexes was found for infectious, circulatory, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
70
0
4

Year Published

1991
1991
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(78 citation statements)
references
References 17 publications
4
70
0
4
Order By: Relevance
“…A similar finding was described in a follow-up study conducted in Rome,6 although an inverse relation has also been described.m An analysis of the rate differences by sex between 1983 and 1990 shows that, in the absence of drug-related mortality, male mortality from all causes would still have risen, while there would have been a clear descending trend for females. However, it may well be that males also have a higher incidence of other pathologies associated with drug use not studied here.6…”
Section: Methodssupporting
confidence: 71%
See 1 more Smart Citation
“…A similar finding was described in a follow-up study conducted in Rome,6 although an inverse relation has also been described.m An analysis of the rate differences by sex between 1983 and 1990 shows that, in the absence of drug-related mortality, male mortality from all causes would still have risen, while there would have been a clear descending trend for females. However, it may well be that males also have a higher incidence of other pathologies associated with drug use not studied here.6…”
Section: Methodssupporting
confidence: 71%
“…The human immunodeficiency virus (HIV) epidemic has altered the classic mortality pattern and further increased mortality rates among drug users. 4,5,6 Unlike studies on alcohol7'8 or tobacco,9'10 studies on illegal drug use and mortality are usually limited to follow-up of drug users and, with few exceptions,1" do not estimate the impact on general mortality. Moreover, routine mortality statistics do not reflect this impact.12 '13 This study estimated the impact of mortality associated with heroin or cocaine consumption on recent mortality trends in the city of Madrid, Spain.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have reported increased mortality among injection drug users enrolled in treatment programs, [1][2][3][4][5] but less is known about the survival of injection drug users not in treatment. Because most injection drug users are not in treatment,6 such information is important for targeting programs designed to reduce mortality among injection drug users.…”
Section: Mortality Among Injection Drug Users Identified As "Out Of Tmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] With the advent of AIDS, injection drug use has become a critical element in HIV transmission; high levels of HIV this issue of the journal. 29 In this simple but elegant study, the authors defined a historical cohort of 4200 injection drug users enrolled in methadone treatment centers in Rome between 1980 and 1988, and then identified deaths occurring in this population during the same time interval through cross-checks with local vital records data and a national mortality registry. Overall and cause-specific mortality rates were calculated for the sample, on the basis of length of follow-up time since enrollment in the methadone centers.…”
mentioning
confidence: 99%
“…18 27,29 Perucci et al did not have information regarding the HIV infection status of their study subjects and were thus unable to examine the relationship between HIV and their cause-specific mortality findings. It is of interest, however, that the observation of increased mortality from malignancies in their population supports the findings of other recent studies among HIV-infected drug users in Italy, in which the occurrence of solid neoplasms and other non-AIDS-defining malignancies has been linked to HIV infection.3536 As also speculated by Perucci et al, these studies suggest that HIV infection, perhaps in conjunction with the heavy use of tobacco and alcohol, may be a risk factor for the development of certain forms of cancer besides those included in the existingAIDS case definitions.37 In addition, the presence of human T-lymphotropic retroviruses types I and II (HTLV-III) has recently been documented in groups of Italian drug users.…”
mentioning
confidence: 99%